Analisis Penerapan Customer Relationship Management dalam Meningkatkan Pelanggan - Suherman, Jajang; M Sarusu, Armansyah; Iin, Iin; Andika, Andika (Jurnal Dimamu, 2025)
Customer Relationship Management (CRM) has now become an important strategy for modern cafes to strengthen relationships with customers and increase loyalty. Social media-based CRM campaigns can boost brand awareness and customer purchase interest. Titik Awal Kopitiam Cafe offers high-quality food, highlighting the concept of a kopitiam or traditional coffee shop, providing various coffee menus and snacks such as toast, rujak cireng, otak-otak, grilled bananas, and others. The problem faced by Titik Awal Kopitiam Cafe is that the points or voucher program is not yet linked to customer IDs and is not yet connected to the marketing department. The use of social media, such as content calendars and message segmentation, which includes promotions, customer testimonials, and educational content, has not been implemented effectively. The purpose of this study is to analyze the number of customers and consumer loyalty, the use of social media, and to analyze growth at Kafe Titik Awal Kopitiam. The method used is applied with a descriptive quantitative approach, conducted directly to observe the implementation of CRM at Kafe Titik Awal Kopitiam, including observation, interviews, and document studies. From the research conducted at Kafe Titik Awal Kopitiam in Jatinangor, in the implementation of CRM and marketing activities, there was a measurable and gradual growth in the customer base, rather than a sudden spike. By placing customers as the main focus, it can maximize customer satisfaction and loyalty and establish strong long-term relationships with customers, while also improving business performance. To drive customer growth. Titik Awal Kopitiam Cafe combines a loyalty program with community activities that trigger word-of-mouth promotion. The community-based approach not only increases loyalty but also encourages existing customers to become brand ambassadors unconsciously. Activities on Instagram and listings on delivery platforms successfully expand reach and can attract new customers.